Enhanced Dichotic Listening and Temporal Sequencing Ability in Early-Blind Individuals - Bae, Eun Bit; Jang, Hyunsook; Shim, Hyun Joon (Frontiers in Psychology, 2022)
Several studies have reported the better auditory performance of early-blind subjects over sighted subjects. However, few studies have compared the auditory functions of both hemispheres or evaluated interhemispheric transfer and binaural integration in blind individuals. Therefore, we evaluated whether there are differences in dichotic listening, auditory temporal sequencing ability, or speech perception in noise (all of which have been used to diagnose central auditory processing disorder) between early-blind subjects and sighted subjects. The study included 23 early-blind subjects and 22 age-matched sighted subjects. In the dichotic listening test (three-digit pair), the early-blind subjects achieved higher scores than the sighted subjects in the left ear (p = 0.003, Bonferroni’s corrected α = 0.05/6 = 0.008), but not in the right ear, indicating a right ear advantage in sighted subjects (p < 0.001) but not in early-blind subjects. In the frequency patterning test (five tones), the early-blind subjects performed better (both ears in the humming response, but the left ear only in the labeling response) than the sighted subjects (p < 0.008, Bonferroni’s corrected α = 0.05/6 = 0.008). Monosyllable perception in noise tended to be better in early-blind subjects than in sighted subjects at a signal-to-noise ratio of −8 (p = 0.054), the results at signal-to-noise ratios of −4, 0, +4, and +8 did not differ. Acoustic change complex responses to /ba/ in babble noise, recorded with electroencephalography, showed a greater N1 peak amplitude at only FC5 electrode under a signal-to-noise ratio of −8 dB and −4 dB in the early-blind subjects than in the sighted subjects (p = 0.004 and p = 0.003, respectively, Bonferroni’s corrected α = 0.05/5 = 0.01). The results of this study revealed early-blind subjects exhibited some advantages in dichotic listening, and temporal sequencing ability compared to those shown in sighted subjects. These advantages may be attributable to the enhanced activity of the central auditory nervous system, especially the right hemisphere function, and the transfer of auditory information between the two hemispheres.